2018
DOI: 10.1002/pon.4668
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between family resilience and posttraumatic growth in breast cancer survivors and caregiver burden

Abstract: Family resilience impacts PTG of breast cancer survivors and caregiver burden. Our findings indicated the necessity of interventions to facilitate family resilience, promote PTG among breast cancer survivors, and decrease family members' caregiver burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 32 publications
(47 reference statements)
8
35
3
1
Order By: Relevance
“…In this study, most of the caregivers were married (76) comparable with other studies (Chindaprasirt et al, 2014;Garlo et al, 2010;Goldstein et al, 2004;Liu et al, 2018;Lukhmana et al, 2015;Seibl-Leven et al, 2018). Married caregivers were less burdened than others (comprising unmarried, widower, and divorced).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, most of the caregivers were married (76) comparable with other studies (Chindaprasirt et al, 2014;Garlo et al, 2010;Goldstein et al, 2004;Liu et al, 2018;Lukhmana et al, 2015;Seibl-Leven et al, 2018). Married caregivers were less burdened than others (comprising unmarried, widower, and divorced).…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, family resilience was positively associated with the survivors' QOL. Though a newly published study has shown family resilience was positively related to PTG (Liu et al, ), no published studies have linked family resilience and PTG to QOL among survivors of breast cancer. Studies have shown that positive family functioning or families’ flexibility in their responses to changes can lead to a better QOL or positive changes in members' mental health (Nam, Kim, DeVylder, & Song, ; Shao‐hua, Jing‐fang, Xue‐feng, & Zhi‐hua, ).…”
Section: Discussionmentioning
confidence: 99%
“…The patients had post-operative chemotherapy and/or radiotherapy for more than one month after surgery to treat their breast cancer. This is part of our cross-sectional study on breast cancer patients and their principal caregivers, more details about the participants and procedure please see our previous article (Liu et al, 2018). Informed consent was obtained from all individual participants included in the study.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, few studies were conducted to promote communication between patients with advanced cancer and their family members. The majority of such studies are limited to breast cancer, prostate cancer and other gender-specific diseases (Greeff & Thiel, 2012;Lim, 2014;Liu et al, 2018).…”
mentioning
confidence: 99%